2022
DOI: 10.1155/2022/3168503
|View full text |Cite
|
Sign up to set email alerts
|

Computer Image Analysis Reveals C-Myc as a Potential Biomarker for Discriminating between Keratoacanthoma and Cutaneous Squamous Cell Carcinoma

Abstract: The distinction between Keratoacanthoma (KA) and Cutaneous Squamous Cell Carcinoma (cSCC) is critical yet usually challenging to discriminate clinically and histopathologically. One approach to differentiate KA from cSCC is through assessing the immunohistochemical staining patterns of the three indicators, β-catenin, C-Myc, and CyclinD1, which are critical molecules that play important roles in the Wnt/β-catenin signaling pathway. Ki-67, as a proliferation biomarker for human tumor cells, was also assessed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…The reduced proliferative capacity of KA was further supported by increased NOTCH signaling and lower levels of MYC activation ( Figure S4 ). These findings agree with previous reports demonstrating inactivating NOTCH mutations in growing KA but not regressing lesions (63,64) and suggest that the KA in our cohort were collected during the terminal differentiation/involution phase rather than the initial growth phase.…”
Section: Resultssupporting
confidence: 94%
“…The reduced proliferative capacity of KA was further supported by increased NOTCH signaling and lower levels of MYC activation ( Figure S4 ). These findings agree with previous reports demonstrating inactivating NOTCH mutations in growing KA but not regressing lesions (63,64) and suggest that the KA in our cohort were collected during the terminal differentiation/involution phase rather than the initial growth phase.…”
Section: Resultssupporting
confidence: 94%
“…The Wnt/β-catenin signaling pathway is an evolutionarily conserved pathway that has been shown to promote tumorigenesis and metastasis in certain cancers, including ESCC [ 35 , 36 ]. Aberrant activation of the Wnt/β-catenin signaling pathway leads to the accumulation of β-catenin in the nucleus, which promotes the transcription of many oncogenes, such as C-myc, CyclinD1 and MMP-2 [ [37] , [38] , [39] ]. Previous studies have found that PRC1 increases lymph node metastasis in lung adenocarcinoma by activating the Wnt/β-catenin signaling pathway [ 21 ].…”
Section: Discussionmentioning
confidence: 99%